Analysis of Service Quality and Price on Visitor Satisfaction of The Indonesia Open 2022 Event - Kusumaningrum, Anisa Putri; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the effect of service quality and price on visitor satisfaction at the Indonesia Open 2022 Event simultaneously and partially. This research uses quantitative methods. The number of samples in this study were 100 respondents. Determination of the sample using purposive sampling technique. The data collection techniques used were questionnaires and literature studies. Based on the test results, it is partially known that the Service Quality variable (X1) affects Visitor Satisfaction (Y) of the Indonesia Open 2022 event, the Price variable (X2) affects Visitor Satisfaction (Y) of the Indonesia Open 2022 event, and simultaneously the Service Quality variable (X1) and Price (X2) simultaneously affect Visitor Satisfaction of the Indonesia Open 2022 Event. The simultaneous coefficient of determination (R2) is 0.436, this means that 43.6% of visitor satisfaction at the Indonesia Open 2022 event is influenced by service quality and price while the remaining 56.4% is influenced by other variables that are outside the variables studied